Design and performance attributes driving mobile travel application engagement. Issue 4 (August 2017) - Fang, Jiaming; Zhao, Zhirong; Wen, Chao; Wang, Ruping
Highlights: Factors and mechanisms affecting mobile travel app engagement are investigated. App design attributes and app performance attributes driving travel app engagement are identified. UI attractiveness and compatibility are the most salient app attributes stimulating engagement. Experiential-cognitive mediation process exists between app attributes and behavioral engagement. Psychological engagement influences behavioral engagement directly and indirectly. Abstract: Increasing people are using mobile applications (apps) for information and activities related to their travel and tourism. Therefore, customer engagement (customer attraction and retention) with mobile travel applications becomes extremely important for travel-related companies. However, there is little empirical research on what factors may drive customers' engagement of using mobile travel apps. This study proposes a research framework, based on the Stimulus-Organism-Response (S-O-R) model, to explore how and to what extent two types of app attributes (i.e., app design and app performance attributes) stimulate travel apps engagement. Based on a user acceptance testing (UAT testing) of a real travel app development project, the study uses survey data from 804 tourists to validate the proposed research model. The results reveal different effectiveness of app design and app performance attributes, and demonstrate that two app design features (i.e., user interface attractiveness and privacy/security) and three app performance attributes (i.e., compatibility, ease of use, and relative advantages) are important drivers of users' behavioral engagement of mobile travel apps. Further, psychological engagement and three types of benefit perception (i.e., hedonic benefit, utilitarian benefit, and social benefit) serially mediate the relationships. The results can be used to improve the related mobile app engagement research and the mobile travel app design.